Call for performing groups, and for papers, workshops, posters, 21ST BIENNIAL WORLD CONFERENCE of International Society for Music Education, Tampa, Florida, USA, 18-23 July 1994 - Tracey, Andrew (International Library of African Music, 1992)
A call is being made for performing groups and recitalists to appear, as well as for papers, workshops and posters to be presented, at the above conference. The theme of the conference is "Music connections: tradition and change". The aim is to present a range of musical traditions to illustrate the breadth of music-making from around the world, including art music, traditional and folk musics, ancient or contemporary musics, jazz and other styles, and in particular music by composers native to the country of origin of the group which illustrates the musical traditions of that country.
Keywords: African Music